SYSTEMATIC LITERATURE REVIEW: PENGARUH MODEL PEMBELAJARAN AUDITORY INTELLECTUALLY REPETITION TERHADAP KEMAMPUAN PEMAHAMAN KONSEP MATEMATIS SISWA - Salsabila, Adinda; Khaerunnisa, Etika; Marethi, Indiana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the effectiveness of the Auditory Intellectual Repetition (AIR) learning model on students' mathematical concept comprehension using the Systematic Literature Review (SLR) method with PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines. The SLR process involves identification, screening, eligibility, and inclusion. Data were obtained from the academic database Google Scholar with the help of the Publish or Perish application. Articles were collected using keywords relevant to the AIR model and mathematical concept comprehension, then selected based on inclusion and exclusion criteria, resulting in 20 articles eligible for analysis. The synthesis of results indicates that the AIR learning model is generally effective in improving students' mathematical concept comprehension compared to conventional learning. This effectiveness is supported by the three stages of AIR: auditory, intellectual, and repetition, which help students gradually grasp concepts. Furthermore, the use of learning media such as GeoGebra, instructional videos, and technology-based applications can enhance the effectiveness of the AIR model. Thus, the AIR model can be an effective learning alternative for improving the quality of mathematics learning, particularly in improving students' understanding of mathematical concepts.